Loss of species and functions in a deforested megadiverse tropical forest - Fuzessy, Lisieux [UNESP]; Pavoine, Sandrine; Cardador, Laura; Maspons, Joan; Sol, Daniel (Wiley, 2024)
Tropical species richness is threatened by habitat degradation associated with land-use conversion, yet the consequences for functional diversity remain little understood. Progress has been hindered by difficulties in obtaining comprehensive species-level trait information to characterize entire assemblages and insufficient appreciation that increasing land-cover heterogeneity potentially compensates for species loss. We examined the impacts of tropical deforestation associated with land-use heterogeneity on bird species richness, functional redundancy, functional diversity, and associated components (i.e., alpha diversity, species dissimilarity, and interaction strength of the relationship between abundance and functional dissimilarity). We analyzed over 200 georeferenced bird assemblages in the Atlantic Forest of Brazil. We characterized the functional role of the species of each assemblage and modeled biodiversity metrics as a function of forest cover and land-cover heterogeneity. Replacement of native Atlantic Forest with a mosaic of land uses (e.g., agriculture, pastures, and urbanization) reduced bird species richness in a nonrandom way. Core forest species, or species considered sensitive to edges, tended to be absent in communities in heterogenous environments. Overall, functional diversity and functional redundancy of bird species were not affected by forest loss. However, birds in highly heterogenous habitats were functionally distinct from birds in forest, suggesting a shift in community composition toward mosaic-exclusive species led by land-cover heterogeneity. Threatened species of the Atlantic Forest did not seem to tolerate degraded and heterogeneous environments; they remained primarily in areas with large forest tracts. Our results shed light on the complex effects of native forest transformation to mosaics of anthropogenic landscapes and emphasize the importance of considering the effects of deforestation and land-use heterogeneity when assessing deforestation effects on Neotropical biodiversity.
Keywords: anthropogenic landscapes; Atlantic rainforest; avian biodiversity; biodiversidad de aves; biodiversidad tropical; bosque Atlántico; diversidad funcional; functional diversity; habitat heterogeneity; habitat loss; heterogeneidad de hábitat; heterogeneidad de paisaje; landscape heterogeneity; paisaje antropogénico; pérdida de hábitat; tropical biodiversity; 人造景观; 功能多样性; 大西洋雨林; 景观异质性; 栖息地丧失; 栖息地异质性; 热带生物多样性; 鸟类生物多样性